2007
DOI: 10.1137/070683908
|View full text |Cite
|
Sign up to set email alerts
|

Convective Stabilization of a Laplacian Moving Boundary Problem with Kinetic Undercooling

Abstract: Abstract. We study the shape stability of disks moving in an external Laplacian field in two dimensions. The problem is motivated by the motion of ionization fronts in streamer-type electric breakdown. It is mathematically equivalent to the motion of a small bubble in a Hele-Shaw cell with a regularization of kinetic undercooling type, namely a mixed Dirichlet-Neumann boundary condition for the Laplacian field on the moving boundary. Using conformal mapping techniques, linear stability analysis of the uniforml… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(61 citation statements)
references
References 20 publications
3
58
0
Order By: Relevance
“…A simple steady solution to the streamer equations given above is a circle translating with constant velocity determined by E ∞ [35,36]. Though such circles differ from proper streamers, which are growing channels of ionized matter [33,[38][39][40], their front half closely resembles the head of the streamer where the growth takes place.…”
Section: E-mail Address: Ebert@cwinl (U Ebert)mentioning
confidence: 99%
See 2 more Smart Citations
“…A simple steady solution to the streamer equations given above is a circle translating with constant velocity determined by E ∞ [35,36]. Though such circles differ from proper streamers, which are growing channels of ionized matter [33,[38][39][40], their front half closely resembles the head of the streamer where the growth takes place.…”
Section: E-mail Address: Ebert@cwinl (U Ebert)mentioning
confidence: 99%
“…In [36], the equation L β = 0 was solved as an initial value problem for the special value = 1. It was found that any initial perturbation β(ω, 0) holomorphic in U ⊃ U ω for τ → ∞ is exponentially convergent to some constant.…”
Section: Formulation Of the Eigenvalue Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar scenario combining linear stability with nonlinear instability was previously found in the problem of two-dimensional void migration [18,25] as well as in the dynamics of ionization fronts [26,27]. The effects of crystalline anisotropy in this problem have not been explored so far.…”
Section: Nonlocal Shape Evolution: Vacancy Islands With Terrace Diffumentioning
confidence: 75%
“…Furthermore, (1.1) is also discussed as a model for certain electrical discharge processes [2,8,9]. Such discharge processes are observed in various natural and experimental settings, e.g.…”
Section: Introduction and Problem Formulationmentioning
confidence: 99%